2000
DOI: 10.1016/s0168-6496(00)00073-8
|View full text |Cite
|
Sign up to set email alerts
|

Identification of novel Archaea in bacterioplankton of a boreal forest lake by phylogenetic analysis and fluorescent in situ hybridization

Abstract: We report here on novel groups of Archaea in the bacterioplankton of a small boreal forest lake studied by the culture-independent analysis of the 16S rRNA genes amplified directly from lake water in combination with fluorescent in situ hybridization (FISH). Polymerase chain reaction products were cloned and 28 of the 160 Archaea clones with around 900-bp-long 16S rRNA gene inserts, were sequenced. Phylogenetic analysis, including 642 Archaea sequences, confirmed that none of the freshwater clones were closely… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
121
1
5

Year Published

2004
2004
2017
2017

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 100 publications
(128 citation statements)
references
References 36 publications
1
121
1
5
Order By: Relevance
“…As only the most abundant archaea were recovered by our method, it should be stressed that the phylogenetic tree represents relationships among the most dominant archaea and does not depict the full extent of archaeal diversity in these soils, which is potentially much greater (Fierer et al, 2007). The majority of the archaeal phylotypes (90.9% of all archaeal sequences) were contained within the group 1.1b crenarchaeotal clade (Jurgens et al, 2000), which has been shown previously to be dominant in soils (Auguet et al, 2009).…”
Section: Resultsmentioning
confidence: 91%
“…As only the most abundant archaea were recovered by our method, it should be stressed that the phylogenetic tree represents relationships among the most dominant archaea and does not depict the full extent of archaeal diversity in these soils, which is potentially much greater (Fierer et al, 2007). The majority of the archaeal phylotypes (90.9% of all archaeal sequences) were contained within the group 1.1b crenarchaeotal clade (Jurgens et al, 2000), which has been shown previously to be dominant in soils (Auguet et al, 2009).…”
Section: Resultsmentioning
confidence: 91%
“…Direct cell count and fluorescent in situ hybridization (FISH) To determine the abundance of bacteria and archaea in collected samples, three oligonucleotide probes were used: EUB338I (Amann et al, 1990), ARCH915 (Amann et al, 1992) and Cren512 (Jü rgens et al, 2000). Filters were fixed on board with formaldehyde (final concentration 4% v/v) for 4 h, washed twice with 1X PBS (phosphate-buffered saline), fixed in 1 ml ethanol : 1X PBS (1:1) and stored at 4 1C until further treatment.…”
Section: Geochemical Analysesmentioning
confidence: 99%
“…doi: 10.1016/j.orggeochem.2006.07.018 diverse settings such as marine and lacustrine water columns and sediments (e.g. DeLong et al, 1994;MacGregor et al, 1997;Schleper et al, 1997;Vetriani et al, 1999;Jurgens et al, 2000;Karner et al, 2001;Keough et al, 2003), peat bogs, wetlands and soils (e.g. Buckley et al, 1998;Ochsenreiter et al, 2003;Sizova et al, 2003;Kotsyurbenko et al, 2004) and the deep subsurface (Takai et al, 2001).…”
Section: Introductionmentioning
confidence: 99%